Comparison of Clinical Trajectories before Initiation of Renal Replacement Therapy between Diabetic Nephropathy and Nephrosclerosis on the KDIGO Guidelines Heat Map - Masanori Abe; Kazuyoshi Okada; Noriaki Maruyama; Hiroyuki Takashima; Osamu Oikawa; Masayoshi Soma (Journal of Diabetes Research)
This study investigated differences between the clinical trajectories of diabetic nephropathy and nephrosclerosis using the Kidney Disease: Improving Global Outcomes (KDIGO) heat map and the clinical characteristics between the two diseases at RRT initiation. This single-center, retrospective study enrolled 100 patients whose estimated glomerular filtration rate (eGFR) was ≥45 mL/min/1.73 m2 at their first visit and who were initiated on RRT. Fifty consecutive patients were assigned to each of the diabetic nephropathy and nephrosclerosis groups. All data for simultaneously measured eGFR and urinary albumin to creatinine ratio (UACR) were collected from first visit to RRT initiation and were plotted on the KDIGO heat map. Diabetic nephropathy was characterized by higher blood pressure and UACR and lower age, eGFR, and serum albumin levels compared with nephrosclerosis at RRT initiation. The vast majority of patients with diabetic nephropathy and eGFR < 60 mL/min/1.73 m2 had concomitant macroalbuminuria, whereas for patients with nephrosclerosis, even when eGFR was <45 mL/min/1.73 m2, many still had normoalbuminuria or microalbuminuria. The rate of decline of eGFR was significantly faster in the diabetic nephropathy group than that in the nephrosclerosis group. The clinical trajectories of diabetic nephropathy and nephrosclerosis differed markedly on the KDIGO heat map.